MODERASI BERAGAMA DALAM BULŪG AL-MARĀM: ANALISIS MUKHTALIF AL-ḤADĪTH DALAM HADIS-HADIS FIKIH - Nadlir, Muhammad Abu; Rochmah, Zahrotur; Firmansyah, Muhammad Aulia Rizal (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
Religious moderation has become a central discourse in contemporary Islamic studies, particularly in plural societies such as Indonesia. This article examines the concept of religious moderation in Bulūg al-Marām by Ibn Ḥajar al-‘Asqalānī through the perspective of mukhtalif al-ḥadīth. The study aims to analyze how seemingly contradictory hadiths in the field of Islamic jurisprudence (fiqh) contribute to a framework of moderation rather than legal rigidity. Employing qualitative library research with a hadith-based analytical approach, this study focuses on selected hadiths related to purification, worship, and social transactions. The findings demonstrate that Ibn Ḥajar’s presentation of conflicting hadiths reflects methodological moderation through reconciliation (al-jam’ wa al-tawfīq), legal plurality (tanawwu’ al-‘ibādah), and contextual reasoning. These principles not only legitimize juristic diversity but also embody ethical moderation rooted in the Prophetic tradition. This study concludes that Bulūg al-Marām provides a normative-hadith foundation for religious moderation that is highly relevant to contemporary socio-religious contexts.